Wave-induced loads on cross-deck of a wave-piercing trimaran with different hull forms of outriggers - Askarian Khoob, Abolfath; Ketabdari, Mohammad Javad (Transport, 2019)
Trimaran has unique hull form with a rapidly growth in recent years due to its application as a mode of transports and naval vessels. Designing trimaran faces many technical challenges because of its complex structural outlines and high-speeds operation. This article investigates the influence of side hulls configuration (symmetric, inboard and outboard types) for wave loads on cross-deck of a trimaran ship when advancing at sea in regular waves. The computation of these hydrodynamic forces is carried out using MAESTRO-Wave 3D panel method code. This code is based on potential flow theory that uses Green’s function with the forward speed correction in the frequency domain. The results demonstrate that the outboard side hull form has the best performance on wave-induced load among three kinds of side hull forms. Furthermore, the results of this study offer more information for selecting the side hull form of the trimaran.